PENGARUH KUALITAS PRODUK, IKLAN DAN PELAYANAN PURNA JUAL TERHADAP KEPUTUSAN PEMBELIAN KENDARAAN BERMOTOR YAMAHA MIO DI SURABAYA - USANTO, JOKO (Kajian Ilmiah Mahasiswa Manajemen, 2012)
Companies in the marketing activities of products, usually can not escape from competition with similar enterprises. One step that can be set so that the company is able to win the competition is to increase promotions to increase sales on a product. Buying behavior one can say something that is unique, because the preferences and attitudes towards the object of every person is different. In addition consumers are from several segments, so that what people want and need is different. Still there are many factors that influence purchasing decisions. This study aims to influence the quality of product, advertising, and after-sales service of the product purchase decision on Yamaha Mio motorcycle community Surabaya. The population in this study is the owner of Mio Yamaha motorcycle in Surabaya sampling technique in this study are non-probability sampling using purposive sampling method is to choose the respondents selected by the researcher based on the characteristics or properties of the previously known population. Analytical techniques used in this study is the multiple linear regression analysis. Based on the obtained results that affect the quality of the product purchase decisions, promotion decisions influence the purchase, after-sales service affects purchasing decisions, and quality of product, advertising, and after-sales service simultaneously significantly influence purchasing decisions.